Educational Supervision at SMP Negeri 58 Palembang - Maretha, Citra (PPSDP International Journal of Education, 2024)
Improving the quality and relevance of education is the most important challenge in educational development. The centralization of administrative and educational management has resulted in the underdevelopment of regional capacity in regulating and managing various educational affairs in each region. One of the most important educational facilities is school. Teachers are human resources who need to continue to be promoted and developed as teaching staff. The potential of teacher resources must continue to be developed so that teachers can carry out their duties professionally. The aim of this article is to understand the educational supervision at SMP Negeri 58 Palembang. This article used a qualitative method with a descriptive approach. Because it is descriptive, the findings of this research will be consulted with theories and previous research results. The results stated educational supervision is needed to monitor and improve the teacher’s teaching and learning process. Educational supervision has a main function which is aimed at improving and increasing the quality of teaching.